An activity space approach to understanding how food access is associated with dietary intake and BMI among urban, low-income African American women. (November 2020) - Raskind, Ilana G.; Kegler, Michelle C.; Girard, Amy Webb; Dunlop, Anne L.; Kramer, Michael R.
Abstract: Inconclusive evidence for how food environments affect health may result from an emphasis on residential neighborhood-based measures of exposure. We used an activity space approach to examine whether 1) measures of food access and 2) associations with diet and BMI differ between residential and activity space food environments among low-income African American women in Atlanta, Georgia (n = 199). Although residential and activity space environments differed across all dimensions of food access, being located farther away from 'unhealthy' outlets was associated with lower BMI in both environments. Future research should move beyond asking whether residential and activity space environments differ, toward examining if, how, and under what conditions these differences impact the estimation of health effects. Highlights: Food access differed between residential neighborhood and activity space measurement approaches. Lower unhealthy food access was associated with lower BMI regardless of measurement approach. The magnitude and significance of associations varied depending on how the activity space was defined.